KEAMANAN DALAM WISATA BAHARI (PENYELAMAN DAN SURFING): TINJAUAN PERMEN PARIWISATA R.I. NO.3 TAHUN 2018 - Muhamad Ali Muchlis (Universitas Nasional, 2019)
Indonesia has many places for diving and surfing. Indonesia is a paradise for tourists to do diving and surfing. The problem then is legal protection for these activities. In 2018 the Minister of Tourism Decree No.3 has accommodated tourism activities for diving and surfing, this will increase protection for tourists. With maximum tourism equipment and management in the field of diving tourism and surfing tourism, it is expected that an increase in the area of tourist visits or tourist destinations and can benefit the community and the country and ensure the preservation of nature.